2015
DOI: 10.7150/jca.10288
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Fracture Pattern in Breast and Gynecologic Cancer Survivors

Abstract: Objective(s): To assess skeletal wide fracture location and time of fracture after cancer treatmentStudy Design: One hundred thirty-nine women diagnosed with breast or gynecologic cancer between 2003 and 2012 that subsequently had a radiologic diagnosis of fracture were identified retrospectively using electronic medical records. Results were compared with skeletal fracture pattern previously reported for a general population.Results: Skeletal fractures in cancer patients occur throughout the entire skeleton s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
0
7
0
2
Order By: Relevance
“…Our results also have implications for understanding the etiology of the increased fracture risk associated with in vivo radiation therapy treatment for cancer [2,8,[60][61][62][63][64][65]. We did not observe any change in mechanical behavior for ex vivo dose levels relevant to radiation therapy (i.e.…”
Section: Discussionmentioning
confidence: 62%
“…Our results also have implications for understanding the etiology of the increased fracture risk associated with in vivo radiation therapy treatment for cancer [2,8,[60][61][62][63][64][65]. We did not observe any change in mechanical behavior for ex vivo dose levels relevant to radiation therapy (i.e.…”
Section: Discussionmentioning
confidence: 62%
“…DECT is feasible for clinical studies since, against conventional wisdom, doses from DECT have been shown to be similar to single energy CT [15, 16]. A quick, accurate, and efficient method to examine both MAT and marrow corrected vBMD would be beneficial to the cancer survivor [17]. The current study is the first to characterize both MAT and accurate vBMD of mineralized tissue throughout the whole body.…”
Section: Introductionmentioning
confidence: 99%
“…Bone marrow fat was associated with vertebral fracture in older adults and postmenopausal women (13). The rapid increase in marrow fat after cytotoxic cancer therapy in pre-clinical studies (14,15) and a recent retrospective clinical study revealing post treatment early fracture events (16) emphasizes the need to assess MF along with bone in cancer patients. However, changes in MF are not readily detected by a traditional dual-energy X-ray absorptiometry (DXA) scan, since DXA only calculates average BMD by superimposing cortical and cancellous BMD.…”
Section: Introductionmentioning
confidence: 99%